Evaluation of pharyngeal airway volume for different dentofacial skeletal patterns using cone-beam computed tomography - Yu-Chuan Tseng; Feng-Chun Tsai; Szu-Ting Chou; Chung-Yao Hsu; Jung-Hsuan Cheng; Chun-Ming Chen (Elsevier, 2021)
Background/purpose: Understanding of the three-dimensional airway space in three skeletal patterns is important in orthodontic treatment. This study investigated differences between the volume of pharyngeal airway sections and the smallest cross-sectional area in three skeletal patterns by using cone-beam computed tomography (CBCT). Materials and methods: The 90 patients were collected to measure total pharyngeal airway volume (TP), velopharyngeal airway volume (VP), glossopharyngeal airway volume (GP), oropharyngeal airway volume (OP), hypopharyngeal airway volume (HP), and the smallest cross-sectional areas (SCA) of the upper respiratory tract as well as other relevant anatomical structures. The mean values differences between classes were analyzed using ANOVA. Pearson's test was used to compare classes in terms of the correlations between different factors. Results: Patients in skeletal classes I and III exhibited significantly higher SCA values (322.6 mm2and 344.5 mm2 respectively) than those in skeletal class II (240.8 mm2). Subjects from skeletal classes I and III exhibited significantly higher values of VP, HP, and OP than those in skeletal class II. Skeletal classes I and III exhibited significantly higher TP values (31190.1 mm3 and 30696.2 mm3, respectively) than those in skeletal class II (22386.0 mm3). Non-significant relationships were discovered between pharyngeal airway and skeletal pattern. Conversely, significant relationships were found between TP and gender, ANB, SNB, hyoid and pogonion positions. Conclusion: The skeletal class II has smaller airway volume than those in skeletal class I and III. The pharyngeal airway volumes could serve as a guide in differentiating the different skeletal classes in clinical settings.